Treatment of metal finishing wastewater in sequencing batch process - Rakmi A. Rahman,; Abu Bakar Mohamad,; Salmijah Surif,; Hassan Basri, (1994)
Metal finishing wastewater contains heavy metals, acids, alkalis, detergents and toxic chemicals such as cyanide far above the Standard B limits of the Environmental Quality (Sewage and Industrial Effluent) Regulation 1979. A sequencing batch process utilising two-tank system was selected to treat such wastewater from a small metal finishing plant in Kuala Lumpur. Treatment with lime and ferrous sulphate complexed and precipitated the cyanide and reduced hexavalent to trivalent chromium which was then precipitated along with other metals as metal hydroxides. The pH of effluent was accordingly adjusted. The pilot plant was designed to run automatically according to a chosen treatment and schedule. The quality of wastewater treated as above was found to meet the Standard B limits